Kasus Malaria Anak-Anak pada Tahun 2019 dan 2022 di Pusat Kesehatan Masyarakat Moru, Kabupaten Alor, Provinsi Nusa Tenggara Timur, Indonesia: Hasil Penelitian - Sanusi, Ali Susanto; Pulinggomang, Bethseba Brontang (PT Kalbe Farma Tbk., 2025)
Introduction: Malaria is an infection transmitted through mosquitoes infected by the Plasmodium parasite, with symptoms such as fever, hepatosplenomegaly, and anemia. Based on the data from Indonesian Basic National Health Survey (RISKESDAS) 2018, malaria prevalence in East Nusa Tenggara Province (ENTP) is the top 3 with a 2% positivity rate with blood tests. Alor district, as a part of ENTP, also an endemic area for malaria and was categorized as a mid-endemic area based on Annual Report of the Indonesian Ministry of Health in 2022. We conducted this study to describe the characteristics of malaria patients, especially in children in Moru Community Health Center (CHC), Alor District, Indonesia. Methods: This descriptive study used data reported on the Malaria Surveillance Information System (SISMAL) from 2019 and 2022. Parameters evaluated in sex, age, type of infection, blood test type, case finding, monthly cases, and area of transmission. Results: There were 33 cases (19,5%) in 2019 and 136 cases (80,5%) in 2022, 46 cases were infected by P. falciparum, 78 by P. vivax, and 45 cases were mixed infections from both plasmodium. Conclusion: Malaria cases in this study increased in April, May, and June, the type of infection was dominated by P. vivax, and most of the infected area was in the Fanating subdistrict.